Pengaruh Live Promote E-Commerce, Pemberian Diskon dan Implusive Buying Terhadap Pengelolaan Keuangan Mahasiswa - Fidyah Jayatri; Dwi Yanuarindah Putri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
E-commerce has transformed consumer purchasing behavior by providing convenient online shopping features, including live promote and discount offers that attract consumers, particularly university students. These features may encourage impulsive buying and affect students’ financial management despite their knowledge of financial principles. This study aims to examine the influence of live promote e-commerce, discount offerings, and impulsive buying on the financial management of students in the Economic Education Study Program at STKIP PGRI Lumajang. A quantitative approach was employed using multiple linear regression analysis. The population consisted of 519 students, with a sample of 130 respondents selected for the study. Data were collected through questionnaires and analyzed using classical assumption tests, multiple linear regression, the coefficient of determination, and hypothesis testing with SPSS version 22. The findings reveal that live promote e-commerce, discount offerings, and impulsive buying each have a positive and significant influence on students’ financial management. Furthermore, these three variables simultaneously have a positive and significant effect on financial management. The study concludes that e-commerce marketing features and consumer behavior are important factors associated with students’ financial management. Therefore, higher education institutions should strengthen financial literacy programs to encourage responsible financial decision-making and improve students’ financial management skills.